Fingerprint matching based on directional image constructed using expanded Haar wavelet transform - Mohd. Mokji, Musa; Syed Abd. Rahman, Syed Abu Bakar (IEEE Computer Society, 2004)
A directional image for a fingerprint obtained from an expanded second stage Haar wavelet transform is presented. This directional image represent the orientation pattern that later on are used for fingerprint matching so that the real owner can be identified. To construct the directional image, we first perform a second stage Haar wavelet transform on a fingerprint. Due to the limitation of the Haar wavelet, we use the expanded version of it instead so that a better directional image can be obtained. Next, we quantize the directional image into a few grey-level values that represent a range of angle orientations. We then smooth the image using an averaging filter. Based on this image we then perform the matching process based on the minimum square error (MSE) criteria.